Contrasting genomic patterns and infection strategies of two co‐existing Bacteroidetes podovirus genera. (18th February 2014) - Holmfeldt, Karin; Howard‐Varona, Cristina; Solonenko, Natalie; Sullivan, Matthew B.
Summary Bacterial viruses (phages) are abundant, ecologically important biological entities. However, our understanding of their impact is limited by model systems that are primarily not well represented in nature, e.g. Enterophages and their hosts. Here, we investigate genomic characteristics and infection strategies among six aquatic Bacteroidetes phages that represent two genera of exceptionally large (∼70–75 kb genome) podoviruses, which were isolated from the same seawater sample using Cellulophaga baltica as host. Quantitative host range studies reveal that these genera have contrasting narrow (specialist) and broad (generalist) host ranges, with one‐step growth curves revealing reduced burst sizes for the generalist phages. Genomic comparisons suggest candidate genes in each genus that might explain this host range variation, as well as provide hypotheses about receptors in the hosts. One generalist phage, φ38:1, was more deeply characterized, as its infection strategy switched from lytic on its original host to either inefficient lytic or lysogenic on an alternative host. If lysogenic, this phage was maintained extrachromosomally in the alternative host and could not be induced by mitomycin C. This work provides fundamental knowledge regarding phage‐host ranges and their genomic drivers while also exploring the 'host environment' as a driver for switching phage replication mode.